Coastal Indebtedness and Impact of Microfinance in Marine FisheriesSector of West Bengal - Vipinkumar, V.P.; Singh, Baldeo; Narayanakumar, R. (Indian Journal of Extension Education, 2011)
The Micro-Finance Institutions (MFI)/Self Help Groups (SHG) mobilised in marine fisheries sector play vital role in reducing the indebtedness among marine fisherfolk. The paper makes an attempt on the assessment of the extent of indebtedness among marine fisherfolk in mechanized, motorized and traditional fisheries sectors and the impact assessment of Microfinance Institutions (MFI) on coastal indebtedness. The study was carried out in two coastal districts of West Bengal state. Situational analysis was done through PLA in the selected locations and the sample respondents were selected from mechanized, motorized and traditional sectors. Data were collected through personal interview from members of 12 selected MFIs and non members in these sectors comprising a total of 600 respondents. The results showed that the level of indebtedness of members of MFIs was less compared to the non members. Even if the indebtedness was more in certain cases, the repayment capacity was found to be significantly improved in MFIs. There is an extreme necessity of strengthening the MFI ventures in the traditional, secondary and tertiary fisheries sectors in the state. A comparative assessment of the sources of credit, the purposes of credit and the utilisation pattern of loans in the state also was undertaken to draw valid conclusions. It was also found that the MFIs ranked better in most of the major attributes in the perception of stakeholders compared to banks and non-institutional credit sources. Success cases of MFIs on entrepreneurial capacity building, those significantly played the role in the debt redemption and poverty alleviation were documented as a practical manual for mobilizing MFIs in any key areas on a sustainable basis.